Ergonomic Evaluation of Foot Operated Rotary Power Generation - Ram, Ramchandra; Kumar, Adarsh; Singh, J K; Jha, S K; Mani, Indra; Ramasubramanian, V (Journal of Agricultural Engineering, 2008)
Large number of farm machines and hand tools used on Indian farms require rotational power for operation. In India, human energy is extensively used as main source of power to operate farm equipment for low power requirement (&lt75 W) in different modes including rotational mode. An ergonomic evaluation of foot operated rotational power generation in different modes namely; pedal, stepper and bicycle at five mechanical output conditions was carried out. During experiments, physiological and postural parameters were evaluated. Up to 55.9W of mechanical power output in bicycle mode of operation was found to be the best. At 74.6W of mechanical power output, stepper mode of operation was better than other modes. At no load and 18.6W of mechanical output, the overall discomfort score was the lowest in bicycle mode. At 37.3,55.9 and 74.6W mechanical outputs, overall discomfort score was lowest in stepper mode. The human efficiency was the highest in bicycle mode of operation at 18.6, 37.3 and 55.9W of mechanical output conditions but at 74.6W mechanical output condition, highest human efficiency was obtained in stepper mode.